Pengembangan Kemampuan Menulis Ilmiah Berbantukan Manajemen Referensi Mendeley Bagi Guru-Guru SMA/Sederajat Di Kabupaten Bintan - Khoirunnisa, Fitriah; Sabekti, Ardi Widhia; Yulita, Inelda (University of Islam Malang, 2020)
A scientific paper containing innovative work in the learning process is needed by teachers as requirement in upgrading their rank in their professional development, including senior high school/equivalent teachers in Bintan Regency. However, generally they get difficulties in making scientific work was caused difficulty in finding relevant reference sources relate to research topic, limited knowledge in information technology and avoid plagiarism check. The purpose of this activity is to guide high school/equivalent teachers in Bintan regency in order to capable to make correct scientific papers good free from plagiarism with the help of Mendeley reference management. Implementation of activities in the form of workshop or training with lecture methods, discussions, question and answer, and projects. The activity was carried out for two days in the form of workshop and two days in the form of independent assignments. This community service activity was considered successful since 80% participants increasing their knowledge of Mendeley's reference management and being able to apply the knowledge in writing free plagiarizm scientific paper.